2019
DOI: 10.1038/s41598-019-40916-9
|View full text |Cite
|
Sign up to set email alerts
|

Facile synthesis of graphene-tin oxide nanocomposite derived from agricultural waste for enhanced antibacterial activity against Pseudomonas aeruginosa

Abstract: Antibacterial screening of graphene-tin oxide nanocomposites synthesized from carbonized wood and coconut shell is investigated against Pseudomonas aeruginosa for the first time. Efficient and facile one step hydrothermal process adopted in the present work for the synthesis of graphene-tin oxide nanoparticles provides an ideal method for the economic large-scale production of the same. Graphene-tin oxide nanocomposites derived from wood charcoal possess a spherical morphology whereas rod like structures are s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(16 citation statements)
references
References 60 publications
0
14
0
Order By: Relevance
“…The prepared material can be used as an excellent candidate for bactericidal applications. [85] The bactericidal property of graphene makes it an ideal candidate to be used in tissue engineering applications.…”
Section: Antibacterialmentioning
confidence: 99%
See 1 more Smart Citation
“…The prepared material can be used as an excellent candidate for bactericidal applications. [85] The bactericidal property of graphene makes it an ideal candidate to be used in tissue engineering applications.…”
Section: Antibacterialmentioning
confidence: 99%
“…The prepared nanohybrid structures were tested against the gram‐negative bacteria Pseudomonas aeruginosa and found that the nanocomposite prepared from the coconut shell shows more antibacterial activity than the graphene tin oxide prepared from the wood charcoal. The prepared material can be used as an excellent candidate for bactericidal applications [85] . The bactericidal property of graphene makes it an ideal candidate to be used in tissue engineering applications.…”
Section: Biomass‐derived Graphene‐based Nanocomposites In Biomedical ...mentioning
confidence: 99%
“…Graphene has been reported to possess significant antimicrobial properties, making it a suitable candidate for the development of new anti-fungal and anti-bacterial chemicals (Wang et al, 2014;Mohan and Panicker, 2019). These microbes are responsible for causing some severe disease infections in plant species resulting in significant yield losses (Mansfield et al, 2012).…”
Section: Antimicrobial Applicationsmentioning
confidence: 99%
“…Some articles discuss only the conventional methods of synthesis (Gorga and Cohen, 2004;Yuan et al, 2009;Rourke et al, 2011;Goenka et al, 2014;Jayasena and Melkote, 2015;Jaleh et al, 2017). Moreover, some articles mentioned the applications of GNCs in the fields of the environment sector (Hao et al, 2012;Cao and Li, 2014;Latha et al, 2016;Luo and Yang, 2017), energy sector (Choi et al, 2010;Kamat, 2010;Dimakis et al, 2015), and agricultural sector (Gomez De Arco et al, 2010;Nuvoli et al, 2011;Fan et al, 2018;Mohan and Panicker, 2019) separately. This review article, however, explored AI-based synthesizing methods and also, a combined approach toward applications in all three sectors is evaluated.…”
Section: Introductionmentioning
confidence: 99%
“…Tin (IV) Oxide (SnO2) is an n-type transparent semiconductor with a wide bandgap of 3.6 eV at 300 K [12,13]. SnO2 is used in a wide variety of applications, including photovoltaic devices [14][15][16][17][18], biological applications [19][20][21][22][23], solar cells [24][25][26][27][28], electrochemical applications [29][30][31], and gas sensors [32][33][34][35][36][37]. Due to its high sensitivity to reducing and oxidizing gases such as CO, H2, and NO, tin oxide is commonly employed in gas sensor applications.…”
Section: Introductionmentioning
confidence: 99%